1996
DOI: 10.1183/09031936.96.09050992
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil activation in fibrosing alveolitis: a comparison of lone cryptogenic fibrosing alveolitis and systemic sclerosis

Abstract: Fibrosing alveolitis complicating systemic sclerosis (FASSc) carries a better prognosis than lone cryptogenic fibrosing alveolitis (CFA). We wanted to determine whether this improved prognosis is associated with differential neutrophil migration and activation in the lower respiratory tract.We therefore compared bronchoalveolar lavage (BAL) neutrophil numbers and levels of neutrophil-derived enzymes in FASSc, CFA and normal individuals. Bronchoalveolar lavage was performed on 45 subjects (FASSc n=20; CFA n=15;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…We obtained similar results when we studied HGF secretion by alveolar neutrophils obtained from ventilated patients with acute lung injury (Jaffre et al, 2002). We hypothesize that the lack of response to LPS is a result of the degranulation of neutrophils when migrating to the alveolar space as previously suggested by others (Cailes et al, 1996). Further studies are needed to confirm this hypothesis.…”
Section: Crestani Et Alsupporting
confidence: 67%
“…We obtained similar results when we studied HGF secretion by alveolar neutrophils obtained from ventilated patients with acute lung injury (Jaffre et al, 2002). We hypothesize that the lack of response to LPS is a result of the degranulation of neutrophils when migrating to the alveolar space as previously suggested by others (Cailes et al, 1996). Further studies are needed to confirm this hypothesis.…”
Section: Crestani Et Alsupporting
confidence: 67%
“…CXCL8 is known to have potent chemotactic activity and has an important role in the accumulation of neutrophils in the lungs of patients with IPF [27] and adult respiratory distress syndrome [28], where persistent neutrophilia is associated with mortality. CXCL8 is able to increase neutrophil adhesiveness and upregulate intercellular adhesion molecule-1 IL-1b pg?mL expression, potentially promoting margination [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that increased numbers of neutrophils in BAL fluid were associated with more severe lung disease (35,36,40). This effect is probably caused by an increased release of proteolytic enzymes and oxygenderived radicals, which in turn, may contribute to the degradation of lung parenchyma (40). In vitro studies have shown that LTB 4 activates neutrophils, which leads to their degranulation, and may therefore contribute to the progression of SLD (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…and the application of LTB 4 results in rapid influx of neutrophils into the lungs (14). In addition, several studies have shown that increased numbers of neutrophils in BAL fluid were associated with more severe lung disease (35,36,40). This effect is probably caused by an increased release of proteolytic enzymes and oxygenderived radicals, which in turn, may contribute to the degradation of lung parenchyma (40).…”
Section: Discussionmentioning
confidence: 99%